The Collagen Family: Biosynthesis and Degradation - Oral Pathologies Induced by Genes Mutations - Goldberg, Michel (The Journal of Dentists, 2020)
Mutations, deletion, insertions, and DNA splicing are involved in many pathologies of the oral sphere. Type I collagen is the major structural protein of bone and dentin. The genetic disease affects more than 1 in 10,000 individuals, and is characterized by fragile bones, skeletal deformities, frequent bone fractures, or even prenatal death. In addition to osteogenesis imperfecta (OI) and dentinogenesis imperfecta (DI), collagen mutations produce Ehlers-Danlos syndrome (EDS), and Alport, Marfan, and Good pasture syndromes. The different forms of the collagen super family include the fibril-forming collagens, collagen forming a network (basement membrane), membrane collagen, and anchoring fibrils. This family of molecules comprises 28 members. For type I collagen collagen is formed by a-chains, cross banded at regular intervals of 67nm. Synthetized as procollagen (with a N- and C-propeptide), the terminal extensions are cleaved by zinc-dependent endopeptidases. Hydroxyproline, hydroxylysine and glycine, are present at every third position. Epidermolysis bullosa are due to collagen gene mutations, or either to the gene coding for cellular cytokeratins (type K5 and/or K14). Mutations are reaching the extra cellular anchoring filaments of the basement membrane (involved in junctional EB),or mutations of the collagen located in the papillary and reticular layers (dystrophic EB - DEB). Osteogenesis imperfecta and some other bone pathologies are detectable in the oral cavity. Mutations od collagens, such as oral submucous fibrosis, diabetes mellitus, kidney and squamous cell carcinoma, are the consequences of genetic diseases involved directly in several areas of the body, or interfering indirectly with the tissues if the oral cavity. Some drugs improve the symptoms of the diseases.